Solidification of radioactive wastes by cement-based materials - Li, Junfeng; Chen, Lei; Wang, Jianlong (Progress in nuclear energy (New series), 2021)
Solidification is the most widely applied treatment method for radioactive waste, and cement is the most commonly used material for the immobilization of radionuclides, due to its advantages, such as high mechanical strength of the solidified waste form, easy operation and low cost. In the past decades, great efforts have been made to improve the cementation technology for enhancing the performance of the solidified waste, including mechanical properties and durability, and for reducing the leaching of radionuclides. Particularly, special cements have been developed based on Portland cement for solidifying radioactive waste. In this review article, various types of cements were briefly introduced, including Portland cement, alkali-activated cement, geopolymer, calcium aluminate cement, and sulphoaluminate cement; the main parameters used to characterize the performance of the solidified waste forms were summarized, such as package capacity, compressive strength, tensile strength, and leaching resistance, and the measures taken to improve these performances were analyzed; the mechanisms for the immobilization of radionuclides in cements were discussed, mainly involving two ways: chemically fixing them in an insoluble form, and physically adsorbing and trapping them in a rigid, durable matrix. This review will deepen the understanding of the principle and application of the solidification of radioactive wastes by various cement-based materials. •The solidification of radioactive wastes by various cement-based materials was reviewed.•Various cements used for solidification of radioactive waste were briefly introduced.•Measures taken to improve the performances of the solidified waste forms were summarized.•Chemical fixation and physical adsorption/inclusion are main mechanism for solidification.